Ciury : powiesc - Gomulicki, Wiktor Teofil, 1850-1919. (Krakow : Wydawn. Literackie, 1986)
A novel picturing life in Warsaw in the second half of the 19th century, with some autobiographical facts from the author.
Keywords: Warsaw (Poland) -- History -- Fiction